Relational database preservation through XML modelling - Ramalho, José Carlos (2007)
Digital Archives are complex structures composed of human resources, state of the art technologies, policies and data. Due to the heritage keeping role that archives assume in our society, it is important to make sure that, the data that is produced by our organizations is preserved accordingly in order do document is activity and provide evidence of their activities. Information stored in an archive must be treated differently than other types of information because it is kept with the purpose of providing evidence of some organizations activity. Due to this fact some properties should be preserved for long periods of time: integrity, liability and authenticity. The preservation of this information extremely complex as digital objects are far from being stable. They are software and hardware dependent. Normally, their auto-preservation period is about 5 years. In this context digital preservation practices become very important and should be part of the institution's planning. The problem is how to keep digital objects in such a way that their information is accessible long past their auto-preservation period. RODA (Repository of Authentic Digital Objects) is a joint venture between public administration and academic researchers that aims to become the public administration repository. A repository where users can rely on digital objects authenticity and where digital objects are expected to endure long beyond the 5 years expectation. For the first prototype three kinds of digital objects were considered: text documents, still images and relational databases. We will focus this paper on the relational databases component. Relational databases ingestion is accomplished by migrating the original database to an XML representation. This representation (DBML - database markup language) was defined according to a series of requisites, trying to preserve database content, database structure and database attributes. Throughout the paper we will discuss the creation of DBML and report its application to some real case studies.